THE ROLE OF ENVIRONMENTAL DEGRADATION IN POPULATION DISPLACEMENT AND CONFLICT IN THE DRYLANDS OF SUBSAHARAN AFRICA (SSA) WITH SPECIAL REFERENCE TO NORTHERN NIGERIA - Andrea Spiess (Sociedade & Natureza)
At present, major parts of Sub-Saharan Africa are seriously threatened by progressivedesertification and in addition continue to face some of the world’s greatest developmentchallenges. More than 200 million people are undernourished, thousands of displaced personsare accommodated in refugee camps and the quality of essential resources such as water,grazing- and arable land are seriously under threat. While income in these regions reliesmainly on natural resources, desertification, caused by anthropogenic activities and enhancedby climatic changes, has massive and negative social, environmental and economic impacts.Once productive drylands are degraded, livelihoods are no longer secure, resources becomeoverexploited, social tension increases, traditional cultural systems collapse and armedconflicts are increasingly driven by resource availability. In the next decades, populationgrowth, rising average resource demand, and persistent inequalities in resource access ensurethat scarcities will affect many environmentally sensitive regions with a severity, speed, andscale unprecedented in history. Approximately 60 million people are expected to eventuallymove from the desertified regions in Sub-Saharan Africa towards North Africa and Europewithin the next 20 years. Long term studies conducted on West Africa on the other handproject a constant migratory flow from Sahelian regions to the coastal cities, such as Lagosand Abidjan, whose population is expected to grow 3.5 times the numbers in 1997 to 271million in 2020.